Lupus nephritis. Part II, modern ideas about therapy - Elena A. Aseeva; Sergey K. Solovyev; Natalia L. Kozlovskaya; Andrey A. Baranov; Evgeny L. Nasonov (Научно-практическая ревматология, 2024)
The second part of the review presents current data on the treatment strategy for lupus nephritis, considering the morphological class of kidney damage, course and activity. Approaches to monitoring and evaluating the effectiveness of treatment, the problems of achieving a complete and partial renal response are described. The characteristic of classical and innovative methods of therapy is given.